Impact of Dimercon on Biochemical Indices in Ovaries of Freshwater Fishes, Labeo rohita and Ctenopharyngodon idella - REDDY, S. JANARDANA; VINEELA, D.; KUMAR, B. KIRAN (IJRDO-Journal of Agriculture and Research (ISSN: 2455-7668), 2016)
The total protein and total amino acid content of ovaries were studied in the freshwater fish; L.rohita and C.idella exposure to various sublethal concentrations of Dimecron (0.0064%, 0.0128%, 0.0192 and 0.0075%, 0.015%, 0.0225%) respectively for different time periods up to 96 hrs. All the concentrations of Dimecron brought about a significantly decrease in total protein and total amino acid content. The results are discussed in relation to the concentration of the most commonly used pesticide in this region.